Il Führer conciato per le feste (Mantichora. Italian Journal of Performance Studies, 2020)
The 20th century has taught us that there are several practises of mortifying a tyrant’s body. Adolf Hitler’s corpse was made to disappear, probably because it was believed that his lifeless body couldn’t be shown without its charismatic power. Nevertheless, the reappearance of his image was soon realized, through practices of ‘ostranenie’, by cinema and literature. Cattelan’s sculpture, Him - that represents a small Hitler bowed down in prayer, with his back to the visitors - and especially its reassessment, in the homonymous play by Fanny & Alexander Theatre Company, are at the heart of this speech, which tries to draw up a comparative inter artes catalogue of the Fuhrer mocked: by putting a baton in the hands of that ‘special’ silhouette-character and by forcing him to ‘dub’, with a perfect lip-synch, all the original cues of The Wizard of Oz movie.